Glutathione S-transferase expression in benign and malignant ovarian tumours. - Green, J. A. (Nature Publishing Group, 1993)
Glutathione S-transferase sub-types alpha, mu and pi were assessed by immunocytochemistry in 109 biopsies of ovarian tissue, comprising malignant epithelial tissue in 86 cases and tissue of ovarian origin considered to be normal in 23. Glutathione S-transferase pi was the most prevalent, being present in all except one malignant epithelium studied and 83% of non-malignant tissue. There were no significant differences in the overall distribution of positive staining for alpha, mu and pi in the malignant and non-malignant biopsies, although the intensity of staining was greater in the malignant epithelium. Stromal staining was in general more pronounced in the malignant biopsies, and this was particularly prominent in the case of the alpha sub-type. Positive staining was seen more frequently in the less well-differentiated tumours, and a diffuse cytoplasmic pattern was the most common observation in tumours of moderate and poor differentiation. There was no significant association between survival and the presence or absence of sub-type staining of alpha and mu sub-type. For the sub-type pi, patient survival was found to correlate with the intensity of staining (on a 0-(+++) scale). Those patients showing resistance to cytotoxic chemotherapy were found to have a higher intensity of staining for GST pi than responding patients. IMAGES: